Effect of dexmedetomidine combined with magnesium sulphate on intracranial tension in patients with severe pre-eclampsia using ultrasonographic optic nerve sheath Diameter - A randomised clinical trial - Enas W. Mahdy; Taghreed E. Sakr; Samar R. Amin (Indian Journal of Anaesthesia)
Background and Aims: Prompt diagnosis and treatment of increased intracranial tension (ICT) critically impact outcomes in patients with severe pre-eclampsia. This study aimed to investigate the influence of dexmedetomidine (DEX) infusion on optic nerve sheath diameter (ONSD), utilised as a surrogate marker for ICT assessment, in pre-eclamptic patients presenting with severe features. Methods: Fifty parturients with a confirmed diagnosis of severe pre-eclampsia were included in the study cohort. Participants were randomly allocated to receive either a DEX infusion 0.2–0.7 μg/kg/h or a matching volume of 0.9% saline as a control, both regimens co-administered with standard magnesium sulphate therapy (4 g loading dose and 1 g/h maintenance). Infusions were continued until surgical completion. The primary outcome was ONSD measured at baseline and at 6, 12, 24, and 48 h post-infusion. Secondary outcomes included haemodynamic variables, sedation scores, neonatal APGAR scores, incidence of adverse events, and length of hospitalisation. Results: Both groups exhibited comparable demographic characteristics. ONSD showed significantly decreased values after DEX infusion compared to baseline (P < 0.05) at all time points. Additionally, haemodynamic variables were significantly reduced compared to baseline in both groups. However, no substantial variations were detected between the two groups. APGAR score, sedation score, length of hospitalisation, and side effects showed no remarkable events, with comparable values between the two groups. Conclusion: Dexmedetomidine infusion in combination with magnesium sulphate effectively mitigates the elevation of intracranial tension observed in pre-eclamptic patients with severe features without increasing maternal or neonatal adverse events.